Preliminary assessment of antifungal activity of lactic acid bacteria from selected malaysian traditional fermented food - Sakina, Shahabudin; Mohd Faizulnazrie, Masri; Mohd Nizam, Lani; Nina Suhaity, Azmi (The Official Publication of The Malaysian Society for Biochemistry & Molecular Biology (MSBMB), 2022)
Candida albicans, naturally a part of a healthy gut and oral microflora, is an opportunistic pathogen that commonly infects humans. However, current antifungal agents are made of synthetic drugs that cause varied adverse effects in patients. This drives efforts to look for natural and safer alternatives to antifungal agents. Fermented food has been studied for its ability to produce lactic acid bacteria with antimicrobial properties. This study examined the antifungal activity of lactic acid bacteria isolated from four traditional Malaysian fermented foods. Pickled chilies, pickled garlic, pickled maman, and tapai were prepared by using homemade recipes and fermented at 4°C. Lactic acid bacteria were isolated from the fermented food during a two-week fermentation on three selective growth agars. During fermentation, bacterial cells were counted at intervals. Growth trends for pickled garlic and pickled chilies presented an exponential phase between days 0 – 4, followed by stationary and death phases between days 8 – 14. Meanwhile, pickled maman and tapai showed continuous growth throughout the 14 days. Antifungal potential of the lactic acid bacteria was assessed via dual agar diffusion assay by spotting pickled water of each fermented food on De Man, Rogosa, Sharpe agar placed above a layer of Sabouraud Dextrose agar with pre-inoculated C. albicans, followed by measurement of the zone of inhibition. Pickled maman produced 1.2 ± 0.05 mm inhibition. In conclusion, pickled maman and tapai produced lactic acid bacteria throughout the two-week fermentation. Based on the dual agar diffusion, pickled maman showed an antifungal potential against C. albicans.